Relationship between Alveolar Ridge Resorption in Mandible and Masticatory Performance Based on Gender in Complete Denture Wearers at Dental and Oral Hospital University Sumatera Utara - Muiz, Abdul; Nasution, Ismet Danial (IIUM Medical Journal Malaysia, 2022)
INTRODUCTION: The aim of the study was to observe the relationship between alveolar ridge resorption in mandible and masticatory performance based on gender in complete denture wearers. MATERIALS AND METHODS: The subjects included were those wearing complete denture between the ages of 45-69 years-old, treated at the Dental and Oral Hospital of University Sumatera Utara. Alveolar ridge resorption in mandible was analysed using the panoramic radiograph and masticatory performance was evaluated clinically using the colour-changeable chewing gum. RESULT: 40 patients were included in this study. 50% were women in which 15 women (37.5%) had mild alveolar ridge resorption whilst 5 (12.5%) had severe alveolar ridge resorption. For masticatory performance, 14 women (35%) had good masticatory performance and 6 (15%) had poor masticatory performance. For the men; 17 (42.5%) had mild alveolar ridge resorption whilst 3 (7.5%) had severe alveolar ridge resorption. For masticatory performance, 16 men (40%) had a good masticatory performance and 4 (10%) had a poor masticatory performance. There was a significant correlation between alveolar ridge resorption in mandible and masticatory performance amongst women (p=0.014). However, there was no significant correlation found between gender and alveolar ridge resorption in mandible (p=0.695), between gender and masticatory performance (p=0.716), and between alveolar ridge resorption in mandible and masticatory performance amongst men (p=0.088). CONCLUSION: The alveolar ridge resorption in mandible is associated with masticatory performance amongst women.